2021
DOI: 10.4103/aja.aja_30_21
|View full text |Cite
|
Sign up to set email alerts
|

PGT or ICSI? The impression of NGS-based PGT outcomes in nonmosaic Klinefelter syndrome

Abstract: This retrospective study demonstrates the clinical outcomes of patients with nonmosaic Klinefelter’s syndrome (KS) who underwent preimplantation genetic testing (PGT) with frozen-thawed testicular spermatozoa. Microdissection testicular sperm extraction (micro-TESE) was performed for sperm retrieval. Next-generation sequencing (NGS) was conducted for embryo analysis. A total of 18 couples aged ≤35 years were included, and 22 oocyte retrieval cycles were completed. Euploidy was detected in 29 of 45 (64.4%) embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Notably, in our study, most chromosomal abnormalities were gonosomal and in particular Klinefelter's, with only a minority being translocations and inversions, in which PGT-A has been shown to reduce miscarriage rate. 44 This finding adds to the controversy as to whether PGT-A should be offered to men with Klinefelter syndrome, 45 although newer technologies such as next-generation sequencing might provide additional benefits in this subgroup of patients. 44 In general, more data are required from future studies to draw a clear conclusion on these still controversial issues, particularly focusing on specific chromosomal anomalies and their effect on pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…Notably, in our study, most chromosomal abnormalities were gonosomal and in particular Klinefelter's, with only a minority being translocations and inversions, in which PGT-A has been shown to reduce miscarriage rate. 44 This finding adds to the controversy as to whether PGT-A should be offered to men with Klinefelter syndrome, 45 although newer technologies such as next-generation sequencing might provide additional benefits in this subgroup of patients. 44 In general, more data are required from future studies to draw a clear conclusion on these still controversial issues, particularly focusing on specific chromosomal anomalies and their effect on pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…Preimplantation genetic diagnosis (PGD) is a clinically feasible technology for testing genetic defects of embryos fertilized in vitro to achieve a pregnancy without genetic disease. It has been developed mainly for couples carrying severe recessive or X-linked Mendelian disorders, structural chromosome abnormalities or mitochondrial disorders ( 15 ), like Klinefelter syndrome, Cystic fibrosis and DMD ( 16 18 ). In addition, it has been reported that early and accurate genetic diagnosis of mutations in DMD could prevent the recurrence of DMD by PGD ( 19 ).…”
Section: Introductionmentioning
confidence: 99%